Paralogous Genes Involved in Embryonic Development: Lessons from the Eye and Other Tissues - Drobek, Michaela (Genes, 2022)
During evolution, gene duplications lead to a naturally increased gene dosage. Duplicated genes can be further retained or eliminated over time by purifying selection pressure. The retention probability is increased by functional diversification and by the acquisition of novel functions. Interestingly, functionally diverged paralogous genes can maintain a certain level of functional redundancy and at least a partial ability to replace each other. In such cases, diversification probably occurred at the level of transcriptional regulation. Nevertheless, some duplicated genes can maintain functional redundancy after duplication and the ability to functionally compensate for the loss of each other. Many of them are involved in proper embryonic development. The development of particular tissues/organs and developmental processes can be more or less sensitive to the overall gene dosage. Alterations in the gene dosage or a decrease below a threshold level may have dramatic phenotypic consequences or even lead to embryonic lethality. The number of functional alleles of particular paralogous genes and their mutual cooperation and interactions influence the gene dosage, and therefore, these factors play a crucial role in development. This review will discuss individual interactions between paralogous genes and gene dosage sensitivity during development. The eye was used as a model system, but other tissues are also included.
Keywords: molekulární evoluce; Gene Duplication; duplication; eye; genová dávka; embryonic development; gene dosage; Gene Dosage; duplikace genu; paralogous genes; Evolution, Molecular